The Byzantine Christ: person, nature, and will in the Christology of Saint Maximus the Confessor - Bathrellos, Demetrios (The Oxford early Christian studies, 2004)
St Maximus the Confessor is one of the giants of Christian theology. His doctrine of two wills was ratified by the Sixth Ecumenical Council in AD 681. This text throws new light upon one of the most interesting periods of historical and systematic theology.